Visualizing the vertical energetic landscape in organic photovoltaics - Lami, Vincent; Weu, Andreas; Zhang, Jiangbin; Chen, Yongsheng; Fei, Zhuping; Heeney, Martin; Friend, Richard H.; Vaynzof, Yana (Joule, 2019)
Summary - Energy level diagrams in organic electronic devices play a crucial role in device performance and interpretation of device physics. In the case of organic solar cells, it has become routine to estimate the photovoltaic gap of the donor-acceptor blend using the energy values measured on the individual blend components, resulting in a poor agreement with the corresponding open-circuit voltage of the device. To address this issue, we developed a method that allows a direct visualization of the vertical energetic landscape in the blend, obtained by combining ultra-violet photoemission spectroscopy and argon cluster etching. We investigate both model and high-performance photovoltaic systems and demonstrate that the resulting photovoltaic gaps are in close agreement with the measured charge transfer (CT) energies and open-circuit voltages. Furthermore, we show that this method allows us to study the evolution of the energetic landscape upon environmental degradation, critically important for understanding degradation mechanisms and development of mitigation strategies.
Gesehen am 30.09.2019